1998
DOI: 10.1084/jem.188.9.1553
|View full text |Cite
|
Sign up to set email alerts
|

Heteroclitic Immunization Induces Tumor Immunity

Abstract: SummaryIn tumor transplantation models in mice, cytotoxic T lymphocytes (CTLs) are typically the primary effector cells. CTLs recognize major histocompatibility complex (MHC) class I-associated peptides expressed by tumors, leading to tumor rejection. Peptides presented by cancer cells can originate from viral proteins, normal self-proteins regulated during differentiation, or altered proteins derived from genetic alterations. However, many tumor peptides recognized by CTLs are poor immunogens, unable to induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
172
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 183 publications
(175 citation statements)
references
References 31 publications
2
172
1
Order By: Relevance
“…Moreover, in the nine fragments recognised as the most immunogeneic of the EC and TM domains according to Ogiso et al (2002), six out of 10 substitutions are conservative. In addition, xenogeneic sequences may give rise to 'heteroclitic' peptides that may have a higher affinity for hamster MHC glycoproteins than homologous peptides (Dyall et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in the nine fragments recognised as the most immunogeneic of the EC and TM domains according to Ogiso et al (2002), six out of 10 substitutions are conservative. In addition, xenogeneic sequences may give rise to 'heteroclitic' peptides that may have a higher affinity for hamster MHC glycoproteins than homologous peptides (Dyall et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Heteroclitic peptides, selected on the basis of in vitro or in silico testing, contain amino-acid substitutions that increase the stability of the peptide/MHC complex and often generate robust cytotoxic T-cell responses that cross-react with the native peptide epitope. [50][51][52][53][54][55] WT1 has emerged as a potentially important target in PCM, after it was shown that the patients who received DLI following T-cell-depleted allo-HCT developed increased WT1-specific T-cell responses post DLI, which were associated with reduction in paraprotein. 56 An ongoing study at the Memorial Sloan-Kettering Cancer Center targets residual myeloma post auto-HCT with a heteroclitic WT1 peptide vaccine combined with three WT1 SLPs and delivered with montanide and GM-CSF adjuvant.…”
Section: Myeloma Vaccinesmentioning
confidence: 99%
“…One mechanism for a heteroclitic response to a peptide epitope is through increased binding of the heteroclitic peptide to MHC molecules, leading to higher affinity (15,(17)(18)(19). The RMA-S stabilization assay was performed to determine relative binding of the D b epitopes used in this study (Fig.…”
Section: To D B Is Abrogated By An Amino Acid Change (N3 W) At Anchormentioning
confidence: 99%
“…This terminology has been applied to other altered peptides with a higher immunological potency than their unaltered counterparts (14 -16). Heteroclitic peptides have increased potency either due to increased binding to MHC molecules (15,(17)(18)(19) or to increased agonist properties to stimulate TCRs (16).…”
mentioning
confidence: 99%